Pandemic Preparedness of Engineers: Efficiency in Engineering and Facility Management - Elix, Kyle Angelique Y. (Animo Repository, 2022)
Throughout the pandemic, facilities management has played a critical role in ensuring the health and safety, longevity, and productivity of enterprises and their employees during these unprecedented times. Management of building systems is crucial for minimizing the spread of the disease and ensuring a safe work environment, so it is more important than ever that the built environment remains working securely and efficiently, regardless of the number of people in a facility. Therefore, the researchers were prompted to quantitatively describe the Roles of Engineers in Pandemic Preparedness regarding the Efficiency Rate of Engineering and Facility Management; the procedure includes gathering information from the participants using survey questionnaires that include engineering and facilities management metrics to measure the mentioned variables before and throughout the outbreak. Thirty (30) participants answered the questionnaire for the reliability testing, and then another group filled out the google forms for the survey proper; afterward, the results underwent statistical treatment. Findings revealed that COVID-19 has afflicted and will likely continue to disrupt subcontractor scheduling and the supply of products. T-test for dependent tool showed a significant difference in the efficiency rates before and during the pandemic relative to engineering and facility management metrics. Pearson Product Moment Correlation also revealed a substantial relationship between the efficiency of implementing safety and health protocols and the efficiency in compliance monitoring and maintenance management during the covid-19 pandemic. Top engineering and facility management issues were reduced accessibility to tools and equipment, adjusting to new work schedules, and other operational terms.